ACADEMIC PERFORMANCE, LEARNING ENVIRONMENT AND SOCIAL SUPPORT INFLUENCING STUDENT LEVELS OF DEPRESSION IN ONLINE LEARNING: A CONCEPTUAL PAPER - Muhammad Ridhwan Mat Zaki; Nur Zarifah Mohamad Nazri, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The COVID-19 pandemic issue has made online learning a requirement in all educational institutions, including schools, colleges, and universities. Even though they face challenges in many ways, teachers and students must adapt to online learning technologies to ensure that it is used as usual. Some of them struggle with anxiety and depression. This study aimed to investigate the factors influencing student levels of depression in online learning. Specifically, the researcher focused on the relationship between academic performance, learning environment, and social support and their impact on students' levels of depression. Students with higher academic performance and a supportive learning environment reported lower levels of depression. Moreover, students who received greater social support from peers, instructors, and family members also reported lower levels of depression. The study contributes to the growing body of literature on the mental health of students in online learning environments by highlighting the importance of academic performance, learning environment, and social support in influencing levels of depression. The study's findings have important implications for educators and policymakers, highlighting the need to prioritize students' mental health and well-being in online learning environments. To improve students' mental health, educators must provide students with a supportive and engaging learning environment that fosters a sense of community and belonging. Additionally, educators should focus on helping students achieve academic success, as this can have a positive impact on their mental health.